Guest Editors' Introduction: Diversity and Inclusion in Different Work Settings: Emerging Patterns, Challenges, and Research Agenda - Theodorakopoulos, Nicholas; Budhwar, Pawan (Human Resource Management, 2015)
The purpose of this article is to analyze and highlight the developments in the current scholarship on managing diversity and inclusion (D&I) and provide insights for future research. While doing so, the article advances our understanding of “what matters” in this field, through the integration of different literature concerning the dimensions of D&I. It also provides a neo‐institutionalist framework, which locates different themes in the D&I scholarship to assist in further development of the field. It argues for a consideration of inquiry in D&I from a neo‐institutionalist perspective to encourage interdisciplinarity and align with broader social science research in human resource management ( HRM ) and development, highlighting the complexity involved in the theorizing of D&I management in organizations. Specifically, we argue for the need to engage with a variety of stakeholders concerned with the management of D&I, to enable cross‐fertilization of theories and mixing methods for future research designs. The article also introduces the manuscripts included in this special issue and build on them as well to develop the future research agenda. © 2015 Wiley Periodicals, Inc.